EVALUATION OF THE PATERN OF ORGANOPHOSPHATE POISONING, TWO YEARS ANALYSIS, 2009-2011DAMMAM POISONING CONTROL CENTRE (PCC), KSA, RETROSPECTIVE COHORT COMMUNITY STUDY - RAGIA M. HEGAZY; HALA F. M. KAMEL (International Journal of Pharma and Bio Sciences, 2015)
Organophosphorus compounds (OPC) are toxic substances that are responsible for the death of thousands of people annually. Objective: The Pattern of acute Organophosphorus poisoning (OPP) in patients admitted to Al-Dammam PCC (poison Control Centre) from 2009-2011. This study was subjected to cases admitted to AL-Dammam PCC, KSA due to OPP. The patients had been divided according to their age, into three groups: below 15 years, above 15 to 40 years, and above 40 years. According to severity, patients were divided into 4 groups. For all patients all of the following parameters were assessed on admission: Pseudo choline esterase (PChE), electrolytes, glucose, and white blood cell (WBC) count . Ninety five patients had been included within this study. The commonest nationality was Saudi (n=45, 47.3%). The commonest route of poisoning was ingestion (57, 6%). The female: male ratio was: 1:2.17. The majority of cases occurred in the summer. The mean age in suicidal (n=17) cases were 22.8±18.1years with Pseudo choline esterase (PChE) level: 95.59±32.13 UKat/L, while in accidental cases (n=78) mean age was 45.8±16.7 with PChE level: 493.61±31.2. Mean PChE levels in severe cases were: 37.95±15.94 U Kat/L with age 42.3±17.7 and 437.25 ±323.92 U Kat/L in mild cases with age 41.7±16.7 years. Most of cases admitted to EMD ward n= 40(42.1%). There was a statistically negative significant correlation between the duration of hospital stay, with PChE levels on admission, (r = - 0.396), and with age (r = - 0.209). There was a strong positive relationship (P<0.001) between duration of hospital stay with severity and suicidal manner. Majority of cases associated with OPP were males and the most encountered route of poisoning was oral route whether within accidental or suicidal manner, PChE levels were significantly correlated with the severity of condition and negatively correlated with the duration of stay in hospital. Recommendation: Health education law enforcement restricting the use of pesticides will reduce OP poisoning.